CORRELATION STUDY AMONG BOILING TEMPERATURE AND HEAT OF VAPORIZATION - UNGUREȘAN, Mihaela L.; PRUTEANU, Lavinia L.; JÄNTSCHI, Lorentz; BOLBOACA, Sorana D. (Studia Universitatis Babeș-Bolyai Chemia, 2016)
In this paper, a preliminary result from a property-property analysis on a series of chemical compounds in regards of quantitative relationship between two properties is communicated. The study was conducted on a series of 190 inorganic chemical compounds for which both properties taken into study are known. The correlation analysis revealed that is a strong relationship between the boiling point and the heat of vaporization at the boiling temperature, having the variance in the paired series of data explained over 90%.